Vulgarisms as a feature of the idiolect of Jakub Żulczyk, based on his novel Wzgórze psów - Chłosta-Zielonka, Joanna (Papers in Linguistics, 2019)
The aim of the article has been to show examples of words with a negative emotional charge – vulgarisms – appearing in the language of the characters in the novel Wzgórze psów by Jakub Żulczyk, as well as to determine the functions they perform in this literary text. There is a close relationship between the presented reality, in which violence prevails, and the language that expresses it. It is difficult to determine the direction of these interactions, because both the language of the characters creates the reality and the reality is presented by the use of language. In the context of the presented examples, the violence conveyed in the statements of the majority of characters is worrying. Żulczyk’s prose shows a negative image of the world, and thus exploits the language resources corresponding to this vision, rich in vulgarisms, demoralizing dialogues and even his descriptions of landscapes do not leave room for any hope.